New Insights in the Pathogenesis of HPV Infection and the Associated Carcinogenic Processes: The Role of Chronic Inflammation and Oxidative Stress. (27th August 2018) - Georgescu, Simona Roxana; Mitran, Cristina Iulia; Mitran, Madalina Irina; Caruntu, Constantin; Sarbu, Maria Isabela; Matei, Clara; Nicolae, Ilinca; Tocut, Sandra Milena; Popa, Mircea Ioan; Tampa, Mircea
Abstract : Human papillomavirus (HPV) is a small double-stranded DNA virus with tropism for epithelial cells. To this date, over 150 genotypes are known and are classified into two major groups, low-risk and high-risk strains, depending on the ability of the virus to induce malignant transformation. The host's immunity plays a central role in the course of the infection; therefore, it may not be clinically manifest or may produce various benign or malignant lesions. The pathogenic mechanisms are complex and incompletely elucidated. Recent research suggests the role of chronic inflammation and oxidative stress (OS) in the pathogenesis of HPV infection and the associated carcinogenic processes. Chronic inflammation induces OS, which in turn promotes the perpetuation of the inflammatory process resulting in the release of numerous molecules which cause cell damage. Reactive oxygen species exert a harmful effect on proteins, lipids, and nucleic acids. Viral oncogenes E5, E6, and E7 are involved in the development of chronic inflammation through various mechanisms. In addition, HPV may interfere with redox homeostasis of host cells, inducing OS which may be involved in the persistence of the infection and play a certain role in viral integration and promotion of carcinogenesis. Knowledge regarding the interplay between chronic inflammation and OS in the pathogenesis of HPV infection and HPV-induced carcinogenesis has important consequences on the development of new therapeutic strategies.